Pendampingan Visualisasi Infografis “IKPA Maksimal” dengan Canva sebagai Media Informasi Peningkatan Pemahaman Satuan Kerja - Ravi Marsa Nugraha; Yuniningsih (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
The bureaucratic reform process requires the creation of maximum service quality improvement, especially in vertical institutions such as the Type A1 Sidoarjo KPPN. Efforts to improve services still face obstacles in the form of difficulties experienced by Work Units in understanding regulations and information delivery mechanisms. This community service program is designed to provide guidance in developing the digitization of information media in the form of infographics, given that infographics have proven to be effective in simplifying and practicalizing the delivery of complex information. This PKM program uses a collaborative mentoring method throughout the four-month internship period (June 23–October 31, 2025) at KPPN Sidoarjo, with four stages: Orientation, Identification, Implementation, and Evaluation. During the identification stage, critical indicators were found in the performance of IKPA for the second quarter of 2025, namely Supply Money Management and TUP, which then became the main targets of intervention. This program produced educational infographics on strategies to increase IKPA value, which were designed using Canva, printed as banners, and displayed in strategic areas. In conclusion, this program successfully maximized communication between employees and Satker through the use of design visualization, improved the ability of KPPN Sidoarjo employees to use digital design applications, and facilitated the delivery of data and regulations to the Work Unit.